Tourist activity of whale watching evaluation in the Área Natural Protegida y Sitio Ramsar Complejo Los Cóbanos, El Salvador - López Martínez, Roxana Margarita; Pineda, Luis; Zetino Calderón, Ana Martha; Aparicio, Josseline Michelle; Sánchez, Jessica Xiomara (Universidad de El Salvador. Secretaría de Investigaciones Científicas, 2023)
Whale watching is a growing tourism industry around the world. Since 2006, whale watch activities have been increasing in El Salvador in the Área Natural Protegida y Sitio Ramsar Complejo Los Cóbanos. This activity has provided an economic alternative to the local fishing community during the seasonal presence of humpback whales (Megaptera novaeangliae), which is the main target cetacean species. The objective of this research was to identify characteristics of whale watch tourism carried out in the Los Cóbanos region. A digital survey was designed that was completed by the service providers for each whale watch tour during the 2021-2022 season, providing information about the profile of the tourist, as well as economic aspects of the activity. In total, 223 whale watch tours were completed in the study period in Los Cóbanos, which amounted to 1465 tourists who visited the area for the sole purpose of whale watching. In economic terms, the 2020-2021 whale season resulted in an additional US$58,829 being brought into the Los Cóbanos economy. The peak of seasonal whale watch activities was between January and February 2021, with 223 tours occurring in those two months alone. Our results show that cetaceans provide a successful economic alternative for the area through whale watch activities. It is essential with such a growing industry that all tourist activity is evaluated, regulated, and managed in an efficient way that allows sustainability, therefore guaranteeing the conservation of the natural resources. This study provides technical tools to aid in the management and regulation of whale watch activities at the government level, and for the continued conservation of cetaceans in El Salvador. En los últimos años el turismo de avistamiento de cetáceos se ha incrementado a nivel mundial. El Salvador ha incursionado en la realización de estas actividades en el Área Natural Protegida y Sitio Ramsar Complejo Los Cóbanos. Esta actividad ha brindado una alternativa económica a la comunidad local en la temporada de ...